Interaction Symbolic Between Heads School and Teacher as Strategy Social For Improving Vocational High School Students' Employability : A Study on Central Vocational High Schools Advantages in Pasuruan Regency /City - Muhadhi Muhadhi; Eddy Sutadji (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to reveal how symbolic interaction between principals and teachers is interpreted as a social strategy in improving the employability of vocational high school students, especially in the Mechanical Engineering Expertise Competence. Using a qualitative case study approach, the research population was conducted at the Center of Excellence Vocational High Schools in Pasuruan Regency/City, while the sample was 4 vocational high schools that have mechanical engineering expertise competencies. Data collection techniques include in-depth interviews, participatory observation, and documentation studies. The results of the study indicate that the symbolic interaction that occurs is not only verbal communication, but also reflects shared values, expectations, and visions in preparing graduates who are adaptive to the world of work. The principal builds meaning through symbols of consistent leadership actions, such as involving teachers in strategic decision-making and instilling an industrial work culture. Teachers, on the other hand, respond to these symbols with more contextual and work-oriented learning practices. This interaction forms a productive school habitus that is the basis for improving student employability